Implementasi ModelImplementasi Modeling Guru dalam Mengembangkan Karakter Tanggung Jawab Anak Usia 5–6 Tahuning Guru dalam Mengembangkan Karakter Tanggung Jawab Anak Usia 5–6 Tahun - Mita Mita; Inten Risna; Yoga Mahendra (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the implementation of teacher modeling in developing the character of responsibility among 5–6-year-old children at RA Khairatul Jannah, Cilegon City. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The findings show that teachers consistently serve as role models through behavioral modeling, value habituation, consistent attitudes, and affirmative communication. Children imitate responsible behaviors demonstrated by teachers, such as completing tasks, maintaining cleanliness, and following classroom rules. The study also found that teacher consistency and emotional closeness significantly contribute to children’s internalization of responsible behavior. However, challenges remain, such as inconsistent home environments and teacher workload that sometimes affects modeling quality. This study concludes that teacher modeling is an effective strategy for strengthening children’s responsibility and should be supported by school programs and collaboration with parents. Recommendations include strengthening teacher training on character-based pedagogy and developing structured habituation programs in PAUD institutions